Back Cover Image, Volume 4, Number 4, July 2022. Issue 4 (13th July 2022) - Hou, Zhen; Xia, Shuixin; Niu, Chaoqun; Pang, Yuepeng; Sun, Hao; Li, Zhiqi; Xu, Yuxi; Zheng, Shiyou
Abstract : Back cover image : Composite polymer electrolytes (CPEs) are regarded as one of the most promising electrolytes for practical commercial applications. However, the unsatisfactory ionic conductivity, limited electrochemical stability and relatively low mechanical strength obstruct the long‐term usage of CPEs‐based batteries. Covalent organic frameworks (COFs) permit atomically precise integration of organic units into extended structure with periodic skeletons and ordered nanopores, providing a new direction in CPEs. In article number 10.1002/cey2.190, Zheng and co‐workers reported that the design of unique COFs, the synthesized COFs powers and the flexible CPEs exhibit in the river of time, which reveal the road of scientific research.